A case of ventricular septal defect and mitral insufficiency after blunt trauma. (September 2014) - Masuoka, Ayumu; Kimura, Naritaka; Katogi, Toshiyuki; Suzuki, Takaaki
Few reports have described traumatic heart injury in children. We describe a case of acute mitral regurgitation associated with papillary muscle rupture, traumatic ventricular septal defect, and impending left ventricular free wall rupture due to blunt trauma in a 2-year-old girl. The papillary muscle was sutured to the left ventricular free wall. The septal defect and surrounding ruptured muscle were covered with a pericardial patch, and a Hemashield patch was used to close the ventriculotomy. A residual defect caused by dehiscence of the pericardial patch necessitated reoperation 10 months later. The patient is currently being observed on an outpatient basis.